2021
DOI: 10.18203/2349-3933.ijam20211046
|View full text |Cite
|
Sign up to set email alerts
|

Role of pleural fluid interleukin-6, neutrophil-lymphocyte ratio, and monocyte-lymphocyte ratio in distinguishing tuberculous and malignant pleural effusions

Abstract: Background: Pleural effusion is caused by various disease, including tuberculosis infection and malignancy. To determine the etiology, immunologic parameters are needed to distinguish tuberculous and malignant pleural effusions, including pleural fluid interleukin-6 (IL-6), neutrophil-lymphocyte ratio (NLR), and monocyte-lymphocyte ratio (MLR).Methods: This was a cross-sectional study, conducted at Sanglah General Hospital in Denpasar from March 2020 to September 2020. Pleural fluid IL-6 and leucocyte differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Singgih et al, reported a similar result, 61.3% of the subject of MPE was female and the mean age of the MPE subject was 71±8.38 years old. 7 There was a substantial number of female subjects with breast, ovarium, and cervix uteri cancer in this study, which could explain this result. According to Deniz et al, malignancy associated with pleural effusion usually occurs in patients older than 50 years old.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Singgih et al, reported a similar result, 61.3% of the subject of MPE was female and the mean age of the MPE subject was 71±8.38 years old. 7 There was a substantial number of female subjects with breast, ovarium, and cervix uteri cancer in this study, which could explain this result. According to Deniz et al, malignancy associated with pleural effusion usually occurs in patients older than 50 years old.…”
Section: Discussionmentioning
confidence: 68%
“…A study by Singgih et al, revealed no significant difference between MPE and tuberculous PE (1,037 (41-34,012) IU/L vs. 583.5 (189-11,469) IU/L; p=0.448). 7 However, Antonagelo et al, showed a significant difference between malignant and tuberculous PE (1,177±675 vs. 1,030±788 IU/L; p=0.003). 18 NMPE groups in our study consisted of exudate and transudate.…”
Section: Discussionmentioning
confidence: 93%